Accounting Conservatism in Times of Crisis: Examining the Effects of Financial Distress and Leverage on Corporate Financial Reporting - Lee, Catrine; Setijaningsih, Herlin Tundjung (International Ecsis Association, 2025)
Accounting conservatism has regained relevance amid global uncertainty, where firms increasingly face financial distress and complex debt structures. However, the extent to which financial distress and leverage affect this principle, and whether profitability moderates these relationships, remains a topic of debate. This study aims to examine the effect of financial distress and leverage on accounting conservatism, while testing the moderating role of profitability. A quantitative design was employed, using financial ratio analysis and panel data regression with a fixed-effect model. The sample comprises 20 food and beverage manufacturing firms listed on the Indonesia Stock Exchange from 2020 to 2023, selected through purposive sampling. Results show that financial distress negatively affects accounting conservatism, suggesting that firms under pressure tend to reduce prudence in order to maintain a favourable performance appearance. Conversely, leverage has a positive effect on conservatism, consistent with creditor monitoring that encourages timely recognition of losses. Profitability, however, neither directly affects conservatism nor moderates the relationship between distress or leverage and the level of conservatism. These findings suggest that profitability does not significantly Influence the impact of financial pressures on reporting practices. The study contributes to ongoing debates by clarifying the inconsistent evidence on the determinants of conservatism in emerging markets. Its implications suggest that regulators and creditors should prioritize monitoring leverage and distress factors rather than relying on profitability as a safeguard. Strengthening covenant structures and disclosure oversight is essential to ensure prudent reporting in financially constrained environments.